1980
DOI: 10.1113/jphysiol.1980.sp013430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetylcholine on membrane currents in guinea‐pig papillary muscle.

Abstract: SUMMARY1. The effect of acetylcholine (ACh) on the membrane current components in guinea-pig papillary muscle was studied by the single sucrose gap voltage clamp method.2. The slow inward current (i.) elicited by various depolarizations from the holding potential of -40 mV was evidently diminished by ACh greater than 5 x 10-7 M. The amplitude of i5, estimated as the difference between the peak of i.and the current at 150 msec, was reduced to 56-8 + 12-9 % (mean + S.D., n = 34) by 2 x 10-6 M-ACh when estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
3

Year Published

1984
1984
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 29 publications
6
29
3
Order By: Relevance
“…8), contrary to what is observed in frog atrial preparations (Giles & Noble, 1976) and in guinea-pig papillary muscle (Hino & Ochi, 1980). isi was decreased by ACh only after it had been increased by pre-treatment with catecholamines.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…8), contrary to what is observed in frog atrial preparations (Giles & Noble, 1976) and in guinea-pig papillary muscle (Hino & Ochi, 1980). isi was decreased by ACh only after it had been increased by pre-treatment with catecholamines.…”
Section: Discussioncontrasting
confidence: 46%
“…Since it has been shown that ACh may also decrease the slow inward current in many preparations (Giles & Noble, 1976;Ten Eick et al 1976;Ikemoto & Goto, 1977;Hino & Ochi, 1980), we also investigated this possible mechanism in rabbit cardiac Purkinje fibres. The effects of ACh on i were studied in the absence and in the presence of adrenergic stimulation.…”
Section: Effects Of Ach On the Slow Inward Currentmentioning
confidence: 99%
“…The other two effects result in changes in inward current flow through separate voltage-dependent channels. Acetylcholine suppresses slow inward current (isi, Brown, 1982) through voltage-dependent calcium channels of both amphibian (Giles & Tsien, 1975;Ikemoto & Goto, 1975; Giles & Noble, 1976) and mammalian cardiac muscle (Ten Eick, Nawath, McDonald & Trautwein, 1976;Hino & Ochi, 1980). In the studies on non-pacemaker tissues, lower concentrations of acetylcholine were required to reduce isi than to activate the potassium current.…”
Section: Introductionmentioning
confidence: 99%
“…The reversal by promazine of acetylcholine-induced changes in rat atrial action potentials (Landmark, Haffner & Lindberg, 1973) and the antagonistic effects of 4-aminopyridine (Freeman, 1979) were interpreted in the same way. The potassium system in ventricular heart muscle is obviously not affected by acetylcholine (Ochi & Hino, 1976;Hino & Ochi, 1980). This may explain why the effects of acetylcholine are inhibited by quinidine in atrial but not in ventricular heart muscle.…”
Section: Discussionmentioning
confidence: 87%
“…TenEick et al (1976) concluded that the enhancement of the potassium conductance is of major importance since the calcium-dependent slow inward current was only inhibited at very high concentrations of acetylcholine. Recently, Ochi & Hino (1978) and Hino & Ochi (1980) described the effects of acetylcholine in guinea-pig ventricular myocardium. These authors found that acetylcholine decreased the calcium-dependent slow inward current without any effect on the potassium conductance.…”
Section: Discussionmentioning
confidence: 99%